Akibat Hukum Perjanjian Pemberian Hibah Tanah Kepada Anak Angkat yang Dibuat Dihadapan Pejabat Pembuat Akta Tanah (PPAT) Menurut Kuh Perdata - N Nursandi; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Analogi Hukum, 2022)
A grant as one of the delivery or levering of an item for free to another person, with consequences without being able to withdraw it which is intended for the benefit of the grantee is one of the legal actions that are quite common in legal subjects in private law traffic. The Civil Code has not explicitly regulated the prerequisites for adopted children as subjects in grants. The problems of this research are: 1. How is the arrangement of granting land to adopted children in the legal regulations in Indonesia; 2. What are the legal consequences arising from the agreement on granting land to adopted children made before the Land Deed Maker Official according to the Civil Code. The results of the study show that the Civil Code stipulates that legal subjects who can carry out land grants are all people who are adults and are capable of carrying out legal actions. The legal consequence of the agreement to grant land grants before PPAT to adopted children who are adults and legally capable is the transfer of ownership rights to the land object of the grant to the adopted children as grantees, where the agreement binds both parties with the PPAT grant deed registered with the National Land Agency.